2020
DOI: 10.1016/j.jebo.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Winner-take-all and proportional-prize contests: Theory and experimental results

Abstract: This study provides a unified framework to compare three canonical types of contests: winnertake-all contests won by the best performer, winner-take-all lotteries where probability of success is proportional to performance, and proportional-prize contests in which rewards are shared in proportion to performance. We derive equilibria and observe outcomes from each contest in a laboratory experiment. Equilibrium and observed efforts are highest in winner-takeall contests. Lotteries and proportional-prize contest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 71 publications
0
34
2
Order By: Relevance
“…Although we only used tournaments in our experiment, we believe that our results are also applicable to other relative performance incentive settings (Cason et al, 2010(Cason et al, , 2019Agranov and Tergiman, 2013;Güth et al, 2016). The tournament winner is determined by calculating the…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we only used tournaments in our experiment, we believe that our results are also applicable to other relative performance incentive settings (Cason et al, 2010(Cason et al, , 2019Agranov and Tergiman, 2013;Güth et al, 2016). The tournament winner is determined by calculating the…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of the team reward also makes the model more generalizable in practice, because businesses increasingly require cooperation among employees from across the organization and the use of group rewards is believed to foster this cooperation (Cohen, 1993;Merchant and Van der Stede, 2007). The Nash 1 Of course, the tournament manager has other ways of designing a tournament by changing the structure of the tournament (Cason et al, 2019), the number of prizes (Orrison et al, 2004;Lim et al, 2009;Müller and Schotter, 2010), the number of players (Orrison et al, 2004), and heterogeneity within the tournament (Weigelt et al, 1989;Cason et al, 2010). equilibrium predicts that free-riding behavior will occur when there are only between-team incentives, and offering within-team incentives should solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Although we only used tournaments in our experiment, we believe that our results are also applicable to other relative performance incentive settings (Cason et al, 2010(Cason et al, , 2019Agranov and Tergiman, 2013;Güth et al, 2016). Group Bonus = 180 points; Individual Bonus = 180 points.…”
Section: Discussionmentioning
confidence: 97%
“…Of course, the tournament manager has other ways of designing a tournament by changing the structure of the tournament(Cason et al, 2019), the number of prizes(Orrison et al, 2004;Lim et al, 2009;Müller and Schotter, 2010), the number of players(Orrison et al, 2004), and heterogeneity within the tournament(Weigelt et al, 1989;Cason et al, 2010).…”
mentioning
confidence: 99%
“…For WTA contests, more risk-averse participants have been found to make significantly lower investments(Millner and Pratt, 1991;Anderson and Freeborn, 2010;Sheremeta and Zhang, 2010;Sheremeta, 2011;Mago, Sheremeta and Yates, 2013;Shupp et al, 2013;Cason, Masters and Sheremeta, Forthcoming), and women have been found to make significantly higher investments(Mago, Sheremeta and Yates, 2013;Brookins and Ryvkin, 2014;Price and Sheremeta, 2015), although these findings are not universal. For PP contests, Cason, Masters and Sheremeta (Forthcoming) report lower investments by risk-averse participants, but there has yet to be a reported association between gender on contest investment in this setting.…”
mentioning
confidence: 95%